Pengaruh Penambahan Serbuk Tongkol Jagung pada Pembuatan Biobriket dari Pelepah Pisang dengan Perekat Tetes Tebu - Dini Kurniawati; Noor Diansyah Januardi; Nur Subekhi (JMPM (Jurnal Material dan Proses Manufaktur), 2018)
Biomass can be used as an alternative fuel such as making biobriquettes. This study aimed to determine the effect of the comparison of mixtures of banana midrib and corn cobs, the effect of molasses used to obtain biobriquettes according to standards, and the results of chemical and physical analysis of its briquettes. The material used in this study were banana midrib and corn cobs which use molasses as an adhesive. The composition variations used were 100: 0 to 10:90. The material was dried to the appropriate moisture content then burned to become charcoal. Those charcoal mixed together according to the composition and were added by 50 grams of molasses. It were pressed and dried. Testing of biobriquette characteristics was carried out by testing moisture content, compressive strength, density, ash content, and calorific value. The result of it was the composition of the material 10:90 with a value of 11.18% moisture content, compressive strength 7,03 kg/cm2, density 0,70 g/cm3, ash content 9,18%, calorific value 4724 kal/g.